Motivational perseverance and its relationship to football teams school results in Wasit - Ahmed Rabie Abdel Ali (Khatulistwa Education Center, 2026)
Background Most educational processes focus on curricula and methods from a theoretical perspective that relies on academic content that deals with student's intellectual processing and does not give balanced importance to student's psychology and psychological factors called student's motivational factors, which can have a greater impact on student's learning and orientation than cognitive ones towards lessons. Objectives Identifying psychological trends and levels of motivational perseverance among students in school teams, and relationship between motivational perseverance and results. From perspective of school students and sports teams. Methods To achieve these objectives, the researcher used descriptive method with a survey approach. The researcher identified research population as 110 students of school football teams in Wasit and selected samples as follows: 10 students for a pilot study, 100 students for construction sample, and 45 students for experimental sample, who were part of the construction sample. After completing scale and extracting scientific foundations, motivational perseverance scale was 48 items distributed across 6 domains. In light of results, guidance program was built according to students' psychological needs. After identifying educational needs, research results were presented, analyzed, and discussed. Results The researcher reached that scale achieved a true measurement of research sample, which helped researcher to know level of students with studied psychological variables and to identify students’ needs, psychological guidance program proved effective in improving motivational perseverance and its relationship to school team results due to changes it brought about in students' knowledge of motivational perseverance and their behavior on field, Significant differences emerged between three groups, favoring second experimental group. Conclusion Among most prominent recommendations mentioned by researcher Physical education teachers were urged to give importance to guidance programs because of their effective role, psychological counseling programs due to their effective role in modifying students' behavior towards other sporting activities.